Anti-corticosteroids combined therapy for treatment of chronic central serous chorioretinopathy - Portes,André Luís Freire (2018)
Abstract The therapeutic impact is described with the combined use of two medications with different anti-corticosteroid actions in the clinical resolution of a patient with chronic central serous chorioretinopathy.